Information inequality in the UK coronavirus communications crisis - Fletcher, R; Kalogeropoulos, A; Simon, F; Nielsen, R (Reuters Institute for the Study of Journalism, 2020)
The coronavirus pandemic is a communications crisis in addition to being a public health emergency. In this report, which describes the results of six online panel surveys of UK respondents fielded from mid-April to late June 2020, we find that: (i) COVID-19 news use has declined significantly from mid-April to late June, (ii) and as news use has fallen, inequalities in COVID-19 news use have grown (in the sense that news use has become unevenly distributed). Furthermore, (iii) offline COVID-19 news use is more widespread than online use, and (iv) online news inequalities are larger than offline news inequalities.